Vitamin D supplementation is associated with reduced immune activation levels in HIV-1-infected patients on suppressive antiretroviral therapy - Fabre-Mersseman, Véronique; Tubiana, Roland; Papagno, Laura; Bayard, Charles; Briceno, Olivia; Fastenackels, Solène; Dudoit, Yasmine; Rostane, Hafeda; Salmon, Dominique; Costagliola, Dominique; Caby, Fabienne; Sauce, Delphine; et al. (AIDS (London), 2014)
A majority of HIV-1-infected patients present a severe deficit in vitamin D, which predicts short-term mortality. Vitamin D is a naturally synthesized hormone, with important immunomodulatory functions. In the general population, its deficit has been associated with increased markers of inflammation. Vitamin D deficit may therefore play a role in the establishment of elevated systemic immune activation, which persists despite suppressive antiretroviral therapy (ART) in HIV-infected patients, and is predictive of disease progression; and vitamin D supplementation may be beneficial in this context. We performed both a cross-sectional study (vitamin D deficit versus normal level) and a longitudinal study (upon vitamin D supplementation for 6 to 12 months) of HIV-1-infected patients receiving suppressive ART. The primary outcome measure was the percentage of activated memory CD8(+) T cells in blood, which is a robust marker associated with disease progression. Secondary outcomes included general T-lymphocyte and B-lymphocyte phenotype. Although vitamin D deficiency had no influence on T-cell and B-cell subset distribution, we found an association between vitamin D and immune activation levels in HIV-1-infected patients. Vitamin D supplementation in vitamin D-deficient patients resulted in reduced immune activation levels. The present data support the rationale of vitamin D supplementation in the routine clinical management of HIV-1-infected patients, in order to decrease immune activation levels and possibly improve long-term survival.